Evaluation of ior ® Leukocim efficacy on patients with Neutropenia. - Ana María Ramos Cedeño; Leslie Pérez Ruiz; Julio Dámaso Fernández Águila; Tamara Guerra; Maritza Cabrera Zamora; Hailen Bobillo López (Medisur)
Bakground: Neutropenia and infections are the most restrictive side effects in chemotherapy application. The granulocytic colonies stimulating factor activates the neutrophils, shortens the neutropenic period and can be effective against the potential risk of infection. There is a need of studies for its commercialization to endorse their effectiveness and security. Objective: To evaluate the impact of the G-CSF in primary and secondary prevention and neutropenia episodes, in onco-haematological patients in Cienfuegos. Method: 95 neutropenic episodes were studied, picked up in clinical histories and data collection notebooks belonging to 47 patients treated in the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos and happened during one year (2005-2006). It was analyzed: demographic data, absolute neutrophils count values, number of administered doses, treatment regime and possible treatment interruptions Results: 50, 5% received treatment in an ambulatory way. There was treatment interruption in 9 episodes, 9,5% and the mean dose number administered to obtain the recovery of neutrophils absolute count was 6,69. Conclusions: The product was effective, sine the decrease of neutropenic episodes could be verified, as the elevation of neutrophil values in approximately one week, what allowed a better pursuit of chemotherapy to patients of the studied series. Abstract To demonstrate the effectiveness of Leukocim an open, phase IV clinical trial was designed, 39 patients from Cienfuegos were evaluated with 73 neutropenic episodes in primary or secondary prophylaxis or treatment, the demographic parameters behaved with an age 49.86 year old average, the predominant sex was the feminine 64.38%, 73.97% belonged to the white race, when the effectiveness was analyzed we obtained that 46.5% received the treatment in an ambulatory way, whereas 52.1% was hospitalized; one patient abandoned before beginning the treatment, the 12,3% of patients abandoned the study, the dose number received in order to correction CAN was between 3 and 7, behaving with a stocking of 1.26 before receiving the treatment and of 5.82 after the same one receiving the next cycle chemo y/o radiotherapy in time demonstrating this way the effectiveness of the product.